EVALUASI TAMAN KOTA SEBAGAI TAMAN KOTA LAYAK ANAK (STUDI KASUS: TAMAN SINGHA MERJOSARI, KOTA MALANG). - Tae, Melania Asbina Kurniati; Djoko, Riyanto; Nailufar, Balqis (Universitas Tribhuwana Tunggadewi, 2019)
City Park is an open area that is able to accommodate the needs of social activities for the community. Other functions of city parks, including. One of these parks is Malang Singha Merjosari Park. However, the forms of utilization for child-friendly city parks are still not functional. Based on the potential and problems, a study is needed to evaluate the function of the park in urban garden design by describing and analyzing the characteristics and design concepts of city parks, confirming respondents opinions and verifying the behavior of city park visitors, and compiling city park recommendations based on evaluation results. The study was conducted at Singha Merjosari Park (TSM), Malang City with the stages of data collection in August 2017. Descriptive analysis was conducted to determine the characteristics of TSM visitors based on questionnaire data. Evaluation is the next step that is carried out by the method of determining the value of the Key performance index (KPI) of the actual conditions of the park based on the design criteria compiled by the experts of the city proper child park. The results of TSM evaluation on the function of child-friendly city parks produce KPI values for physical components of 0.77, garden space components of 0.75, garden quality components of 0.75, garden element components of 0.76, and user activity components of 0.77. The total KPI value of all components is 0.77 with a value scale of 0-1. The results of confirmation of visitors activities and their perceptions of child-friendly city parks stated that there was an influence on the childrens decent city. Recommendations are given based on the results of the KPI value recapitulation of each component with the results of the respondents opinion confirmation and verification of visitor behavior. Taman kota merupakan area terbuka yang mampu mengakomodasi kebutuhan aktivitas sosial bagi masyarakat. Fungsi lain dari taman kota, di antaranya, sebagai area ekologis dan estetika perkotaan. Salah satu taman tersebut adalah Taman Singha Merjosari Kota Malang. Namun, bentuk-bentuk pemanfaatan untuk taman kota layak anak masih belum fungsional. Penelitian dilakukan di Taman Singha Merjosari ( TSM), Kota Malang dengan tahapan pengumpulan data pada agustus 2017. Analisis deskriptif dilakukan untuk menentukan karakteristik pengunjung TSM berdasarkan data kuesioner. Evaluasi merupakan tahapan selanjutnya yang dilakukan dengan metode penentuan nilai Key performance index ( KPI) dari kondisi aktual taman berdasarkan kriteria desain yang disusun dari para ahli taman kota layak anak. Hasil evaluasi TSM terhadap fungsi taman kota layak anak menghasilkan nilai KPI untuk komponen fisik sebesar 0.77, komponen ruang-ruang taman sebesar 0.75, komponen kualitas taman sebesar 0.75, komponen elemen taman sebesar 0.76, dan komponen aktivitas pengguna sebesar 0.77. Nilai total KPI dari seluruh komponen dihasilkan sebesar 0.77 dengan skala nilai 0-1. Hasil konfirmasi aktivitas pengunjung dan persepsinya terhadap taman kota layak anak menyatakan adanya pengaruh terhadap kota layak anak. Rekomendasi diberikan berdasarkan hasil rekapitulasi nilai KPI tiap komponen dengan hasil konfirmasi pendapat responden dan verifikasi perilaku pengunjung.